Implementasi Metode User Centered Design Pada Sistem Pendukung Keputusan Peramalan Penjualan Ikan Hias - Linda Perdana Wanti; Kurniawan Yogi Laksono; Riyadi Purwanto (Jurnal ICT : Information Communication & Technology, 2019)
Strategies in sales are needed to increase sales of goods and increase company profits. One of them is sales forecasting that predicts future sales, to avoid mistakes in the supply of goods sold. This study aims to help shop owners make decisions in determining the supply of ornamental fish stocks. The implementation of the user-centered design method for decision support systems used to forecast the sale of ornamental fish by processing ornamental fish sales data in the previous period to obtain sales predictions in the next period. The method implemented is a user-centered design method wherein the process of making a decision support system always involves the user, in this case, the shop owner as of the application user. The user-centered design approach helps in designing technology-based information systems that are user-centered and the goal of user-centered design is not only to create systems /applications that are useful for the user. Data collection was used to create a decision support system using literature studies, interviews with business owners and questionnaires. The results of research on decision support systems are forecasting the sale of ornamental fish with a decision support system using two methods, namely the trend moment method to help shop owners determine the fish stock and user-centered design methods to design a decision support system that suits the needs and wishes of the user